2007
DOI: 10.1007/s10495-006-0580-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of PKCζ in amikacin-induced apoptosis in the cochlea: Prevention by aspirin

Abstract: Aminoglycoside antibiotics are ototoxic, inducing irreversible sensorineural hearing loss mediated by oxidative and excitotoxic stresses. The NF-kappaB pathway is involved in the response to aminoglycoside damage in the cochlea. However, the molecular mechanisms of this ototoxicity remain unclear. We investigated the expression of PKCzeta, a key regulator of NF-kappaB activation, in response to aminoglycoside treatment. Amikacin induced PKCzeta cleavage and nuclear translocation. These events were concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…In the lateral line, aminoglycoside-induced hair cell death is independent of caspase activation, implicating this caspase-independent role of Xiap in gentamicin damage ( Coffin et al, 2013b ). AIF translocates from the mitochondria to the nucleus in damaged cells, and AIF translocation is reported in hair cells in response to amikacin administration in vivo or to gentamicin in vitro , suggesting that AIF may mediate hair cell damage ( Lecain et al, 2007 ; Zhang et al, 2012 ). However, an in vivo study in mice did not find AIF translocation after kanamycin ototoxicity, but did note a decrease in cochlear AIF expression ( Jiang et al, 2006a ).…”
Section: Discussionmentioning
confidence: 99%
“…In the lateral line, aminoglycoside-induced hair cell death is independent of caspase activation, implicating this caspase-independent role of Xiap in gentamicin damage ( Coffin et al, 2013b ). AIF translocates from the mitochondria to the nucleus in damaged cells, and AIF translocation is reported in hair cells in response to amikacin administration in vivo or to gentamicin in vitro , suggesting that AIF may mediate hair cell damage ( Lecain et al, 2007 ; Zhang et al, 2012 ). However, an in vivo study in mice did not find AIF translocation after kanamycin ototoxicity, but did note a decrease in cochlear AIF expression ( Jiang et al, 2006a ).…”
Section: Discussionmentioning
confidence: 99%
“…ASA prevents cleavage of PKC zeta, a key regulator of NF κβ activated by exposure to amikacin [199]. Systemic administration of ASA effectively protects guinea pigs from gentamicin-induced hearing loss [200].…”
Section: Efforts In Hair Cell Protectionmentioning
confidence: 99%
“…Numerous in vivo and in vitro studies have demonstrated that Amikacin caused hair cell death and aberration of hearing thresholds and/or hearing levels [ 28 29 30 31 32 33 34 35 36 37 ]. In our study, group 1 (AK) had significant decreases of DPOAE amplitudes on days 7 and 15 as compared to initial DPOAE amplitudes, and our findings are compatible with relevant literature.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with numerous agents were conducted in recent years in search of a prevention for amikacin-induced ototoxicity [ 28 29 30 31 32 33 34 35 36 37 ] ( Table 2 ). Research on this issue was accelerated especially during the last decade, but currently there is no agent in use (for counteracting AK's ototoxic effects) that has achieved general consensus.…”
Section: Discussionmentioning
confidence: 99%